2019
DOI: 10.15766/mep_2374-8265.10867
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Telemedicine OSCE (TeleOSCE): A Simulated Standardized Patient Video-Visit Case for Clerkship Students

Abstract: Introduction: Telemedicine is a growing practice with minimal training in US medical schools. Telemedicine OSCE (TeleOSCE) simulations allow students to practice this type of patient interaction in a standardized way. Methods: The Insomnia-Rural TeleOSCE was implemented as part of a required clinical clerkship for students in their second, third, or fourth year of medical school. This case addressed a patient with depression in a medically underserved area. Students performed it as a formative experience and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 5 publications
2
86
0
2
Order By: Relevance
“…In addition to practical guidelines for those undertaking telemedicine practice, there is urgent need for the rigorous translation and evaluation of "core" trainee competencies into virtual care environments. Until recently, the majority of telemedicine curricula and learner evaluation has focused on technical proficiency or adapted history and exam skills [18][19][20] . While domains such as professionalism, communication, and other interpersonal skills are often asked of evaluators as part of a general evaluation of trainees, these domains are rarely explicitly adapted to the virtual encounter.…”
Section: Recommendations For the Training Of Residents During The Covmentioning
confidence: 99%
“…In addition to practical guidelines for those undertaking telemedicine practice, there is urgent need for the rigorous translation and evaluation of "core" trainee competencies into virtual care environments. Until recently, the majority of telemedicine curricula and learner evaluation has focused on technical proficiency or adapted history and exam skills [18][19][20] . While domains such as professionalism, communication, and other interpersonal skills are often asked of evaluators as part of a general evaluation of trainees, these domains are rarely explicitly adapted to the virtual encounter.…”
Section: Recommendations For the Training Of Residents During The Covmentioning
confidence: 99%
“…11 Although objective structured clinical examinations (OSCEs) have been used in telehealth training, most interventions are limited to single encounter e-visits at the undergraduate medical level of training. [12][13][14] Only one study reported that an OSCE with nurse practitioners and occupational/physical therapy students utilized an interdisciplinary teaching model. 15 Primary care can be challenging, and for patients with complex psychosocial needs, we should use interdisciplinary telehealth modalities to manage patients.…”
Section: Introductionmentioning
confidence: 99%
“…Use of online role plays offers an interesting way to expose students to telemedicine and tele-supervision which are rarely addressed during undergraduate training. 18 Tutors quickly adapted to such changes, although they reported facing more technical difficulties than students in using new IT tools. This may be related to tutors having to perform substantially more handling of technical aspects (sharing a video, use of whiteboard, etc.)…”
Section: Discussionmentioning
confidence: 99%